Temperature tolerance and potential impacts of climate change on marine and estuarine organisms - Madeira, Diana Sofia Gusmão Coito, 1988- (2011)
Tese de mestrado. Biologia (Ecologia Marinha)Universidade de Lisboa, Faculdade de Ciências, 2011